An emerging evidence base for the management of neonatal hypoglycaemia. (January 2017) - Harding, Jane E; Harris, Deborah L; Hegarty, Joanne E; Alsweiler, Jane M; McKinlay, Christopher JD
Abstract: Neonatal hypoglycaemia is common, and screening and treatment of babies considered at risk is widespread, despite there being little reliable evidence upon which to base management decisions. Although there is now evidence about which babies are at greatest risk, the threshold for diagnosis, best approach to treatment and later outcomes all remain uncertain. Recent studies suggest that treatment with dextrose gel is safe and effective and may help support breast feeding. Thresholds for intervention require a wide margin of safety in light of information that babies with glycaemic instability and with low glucose concentrations may be associated with a higher risk of later higher order cognitive and learning problems. Randomised trials are urgently needed to inform optimal thresholds for intervention and appropriate treatment strategies.